Вінерів процес у евклідовому просторі з мембраною на даній гіперплощині - Копитко, Б.І.; Портенко, М.І. (Доповіді НАН України, 2022)
Побудовано вінерів процес у евклідовому просторі з мембраною на заданій гіперплощині такою, що її коефіцієнт пропускання є вимірною функцією зі значеннями в проміжку [–1, 1], та доведено теорему про граничний розподіл кількості перетинів мембрани дискретною апроксимацією цього процесу за умови, що величина кроку дискретизації часу прямує до нуля. У випадку пористої мембрани граничний розподіл допускає прозору інтерпретацію. For the Brownian motion in a Euclidean space, a membrane located on a given hyperplane and acting in the normal direction is constructed such that its so-called permeability coefficient can be given by an arbitrary measurable function defined on that hyperplane and taking on its values in the interval [–1, 1]. In all the previous investigations on the topic that coefficient was supposed to be a continuous function. A limit theorem for the number of crossings of the hyperplane by a discrete approximation of the process constructed is proved. A curious interpretation for the limit distribution in that theorem can be given in the case of the membrane being porous.